2014
DOI: 10.1155/2014/897214
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Studies Applying Cytokine-Induced Killer Cells for the Treatment of Gastrointestinal Tumors

Abstract: Tumors of the gastrointestinal system represent a significant share of solid tumors worldwide. Despite the advances in diagnosis and treatment, the prognosis of gastrointestinal tumors is still very poor and improved therapies are indispensable. Cytokine-induced killer (CIK) cells are feasible for an immunotherapeutic approach as they are easily available and have an advantageous biologic profile; they are rapidly proliferating and their high cytotoxicity is non-MHC-restricted. We summarize and discuss twenty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…CIK cells are a subset of natural killer T lymphocytes (NKTs) that are type II NKT cells (20) with enhanced tumor cell lytic activity (21), higher proliferation rate (22), and relatively lower toxicity (23). Due to these characteristics, CIKs are extensively used in antitumor therapy in clinics (24)(25)(26). In this study, the influence of DCs on CIKs was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…CIK cells are a subset of natural killer T lymphocytes (NKTs) that are type II NKT cells (20) with enhanced tumor cell lytic activity (21), higher proliferation rate (22), and relatively lower toxicity (23). Due to these characteristics, CIKs are extensively used in antitumor therapy in clinics (24)(25)(26). In this study, the influence of DCs on CIKs was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that CD3 + and CD3 + CD8 + T lymphocytes represented more than 90% and 60% of the total EAAL cells, respectively, while the proportions of CD3 + CD4 + and CD3−CD16 + /CD56 + NK cells were relatively lower. The proportions of CD8 + CD28 + cytotoxic T lymphocytes (CTL) and CD3+CD16+/CD56+ T lymphocytes, which are essential effector cells and play an important role in anti-tumor immunity Jakel et al, 2014;, and which account for (38.38±11.15)% and (34.48±16.41)%, respectively, were also very high in EAAL cells. Therefore, the high content described above for these cell types in EAAL may result in increased antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…CIK cells represent a promising immunotherapy for the treatment of gastrointestinal tumors (Jakel et al, 2014). Adjuvant transfusion of CIK cells prolongs DFS in patients with colorectal cancer from 29.35 ± 6.39 % in control without CIK cells to 59.65 ± 24.80 % with CIK transfusion, and no immediate adverse reactions to the CIK cell transfusions (Zhu et al, 2013).…”
Section: Clinical Trialsmentioning
confidence: 99%